Peaceful Existence of Tumor Cells with Their Non-malignant Neighbors: The Trade of Tumor Cells with Tumor Microenvironment - Maali, Amirhosein; Sarfi, Mohammad; Mirzakhani, Mohammad; Goodarzi, Golnaz; Maghsoudi, Hosein; Maniati, Mahmood; Tehrani, Sadra S.; Qujeq, Durdi (Current Chemical Biology, 2020)
Tumor cell growth and survival are the outcomes of communication between tumor cells and tumor microenvironment (TME). In other words, tumor cell growth and survival are greatly affected by the interaction between adjacent cells and tumor cells. In this paper, we review the recent advances in studies of TME, including metabolic interplays between tumor cells and their non-malignant neighbors (peaceful interaction and autophagy), trades of signaling pathways (approach to most important ones; cytokine pathway, NF-kB pathway, intra-tumoral hypoxia, oxidative stress, and nitric oxide-depended pathways), miRNAs (as the regulatory molecules which are present in TME), and Tumor-associated Exosomes (TAEs). Characterization of TME bio-molecules, nutrient changes, and cellular and molecular interactions help to clarify the progression of cancer and find novel targets for the treatment of cancer.
Keywords: Tumor microenvironment